Cross-sector collaboration to reduce health inequalities: a qualitative study of local collaboration between health care, social services, and other sectors under health system reforms in England - Hugh Alderwick; Andrew Hutchings; Nicholas Mays (BMC, 2024)
Abstract Background Policymakers across countries promote cross-sector collaboration as a route to improving health and health equity. In England, major health system reforms in 2022 established 42 integrated care systems (ICSs)-area-based partnerships between health care, social care, public health, and other sectors-to plan and coordinate local services. ICSs cover the whole of England and have been given explicit policy objectives to reduce health inequalities, alongside other national priorities. Methods We used qualitative methods to understand how local health care and social services organizations are collaborating to reduce health inequalities under England's reforms. We conducted in-depth interviews between August and December 2022-soon after the reforms were implemented-with 32 senior leaders from NHS, social care, public health, and community-based organizations in three ICSs experiencing high levels of socioeconomic deprivation. We used a framework based on international evidence on cross-sector collaboration to help analyse the data. Results Leaders described strong commitment to working together to reduce health inequalities, but faced a combination of conceptual, cultural, capacity, and other challenges in doing so. A mix of factors shaped local collaboration-from how national policy aims are defined and understood, to the resources and relationships among local organizations to deliver them. These factors interact and have varying influence. The national policy context played a dominant role in shaping local collaboration experiences-frequently making it harder not easier. Organizational restructuring to establish ICSs also caused major disruption, with unintended effects on the partnership working it aimed to promote. Conclusions The major influences on cross-sector collaboration in England mirror key areas identified in international research, offering opportunities for learning between countries. But our data highlight the pervasive-frequently perverse-influence of national policy on local collaboration in England. National policymakers risked undermining their own reforms. Closer alignment between policy, process, and resources to reduce health inequalities is likely needed to avoid policy failure as ICSs evolve.